Constructing the Boundaries of Retirement for Baby-Boomer Women: Like Turning Off the Tap, or Is It? - van den Hoonaard, Deborah K. (Qualitative Sociology Review, 2015)
We are at a unique point in history when an unprecedented number of women are beginning to retire. Earlier work has suggested that women have few identity concerns in retirement because they had less attachment to the labor force. In contrast, women of the baby-boomer generation are the first cohorts to have participated in significant numbers in the paid work force since the institutionalization of retirement.Using in-depth, semi-structured interviews, this article explores baby-boomer women’s process of leaving the paid work force and queries what retirement means to them. It focuses on the eroding boundary between work and retirement and issues of personal and social identity for the research participants. When women retire, they navigate a number of key boundaries between full-time, paid and other work and between their own transitions and the transitions of others in their lives. The women’s social identity reflects their experience of the intersection of retirement, aging, and gender. The themes that permeate the interviews include the loss of a primary identity without having a new positive identity to claim, being retired as a conversation stopper, and experiencing the invisibility that often comes with aging. Developing a unique identity and finding new meaning as a retiree is a challenging process for baby-boomer women as they negotiate “lingering identities” to avoid crossing the identity boundary from professional to retired. The article uses the words of the research participants to explore how they construct boundaries between work and retirement, the extent of their permeability, and the impact of women’s relationships and identity on those boundaries.